Species discovery in Southern African bee flies (Diptera, Bombyliidae): A new species in the revised genus Enica Macquart, 1834 - Lisa Rollinson; Allan Cabrero (African Invertebrates)
The Bombyliidae genera Enica Macquart, 1834 and Nomalonia Rondani, 1863, restricted to South Africa, are synonymized. Currently, one species of Enica is known from South Africa, Enica longirostris (Wiedemann, 1819), and six Nomalonia species are newly combined with Enica: Enica clavicornis (Hesse, 1956), comb. nov.; Enica eremophila, (Hesse, 1975), comb. nov.; Enica henicoides (Hesse, 1956), comb. nov.; Enica imitata (Hesse, 1956), comb. nov.; Enica sporanthera (Hesse, 1956), comb. nov.; and Enica syrticola (Hesse, 1956), comb. nov. A new species, Enica adelphe sp. nov. from the Richtersveld in the Northern Cape of South Africa, is described. All Enica species are redescribed and a dichotomous key with photographic references is provided for ease of identification. Specimen occurrence data and photographs are provided for each species. Each species of Enica occurs in at least one of three biodiversity hotspots in South Africa, i.e., Succulent Karoo, Cape Floristic Region, and Maputaland-Pondoland-Albany, with E. longirostris occurring in all three.